Use and utility of endocrine multidisciplinary tumour board: an appraisal from a tertiary centre - Sparano, Clotilde; Canu, Letizia; Perigli, Giuliano; Santoro, Roberto; Pradella, Silvia; Grazzini, Giulia; Mangoni, Monica; Simontacchi, Gabriele; Fibbi, Benedetta; Vezzosi, Vania; Olianti, Catia; Maggi, Mario; et al. (Frontiers in Endocrinology, 2025)
IntroductionThe Endocrine Multidisciplinary Tumour Board (EMTB) is a specialised board for endocrine tumours, including thyroid, adrenal, and rare endocrine neoplasms. Although required by major guidelines, little is known about the current EMTB composition and working outcomes. The present study aims to analyse the use and support provided by an experienced EMTB, highlighting the skills of this board.MethodsThis monocentric and retrospective study considered all the cases discussed (N=1038, concerning 835 patients) within the ETMB of Careggi University Hospital of Florence from January 1st, 2021, to December 31st, 2023. The queries have been standardised into five major groups. Besides treatment and follow-up indications, particular attention has been paid to the need for repeated discussions, additional indications, imaging revisions, and overall survival (OS) outcomes.ResultsThyroid and rare cancers were the most frequently represented (64% and 32%, respectively). At logistic regression analysis, the need for multiple discussions was associated with being a rare disease (p<0.001), familiar syndrome (p=0.003), or adrenal masses (p=0.005). When the query was "imaging review," external imaging was more often re-evaluated (p=0.027) due to differing results at EMTB revision, and in about 51% of these cases, further insights were requested. Compared to external control groups, Anaplastic Thyroid Carcinoma and Adrenocortical Carcinoma showed improved OS, 7.84 vs 2.46 months (p=0.049) and 51.92 vs 26.17 months (p=0.0076), respectively. From the hormonal perspective, further hormonal investigations were required in about 16% of eligible cases.ConclusionsEMTB is pivotal in managing and optimising common and rare endocrine tumour workups.